ADAPTASI JURNALIS MEDIA ONLINE DI MASA PANDEMI COVID-19 - Vinanda, Rufki Ade; Azmi , Bela Fataya (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The COVID-19 pandemic that occurred some time ago has become a disruption that has harmed journalists' work. It is equally known that journalism jobs require mobility and a high level of interaction. However, during the COVID-19 pandemic, journalists' movement became limited. In this research, the author focuses on how journalists adapted to carrying out their work during the Pandemic in 2020. This research uses a qualitative case study approach with in-depth interviews. More specifically, the research focuses on online mainstream journalistic media as the research subject. Online media were specifically chosen as the research subject, considering that in the digital era, online media have become one of society's main sources of information. During the COVID-19 pandemic, mainstream media became the front guard as a public information source. The sources for this research consisted of nine journalists from four national online media, namely Detik.com, Tribunnews.com, Suara.com, and VOI.id. This research found that journalists adapted to cover news during the Pandemic, including reducing offline coverage, increasing online coverage and adjusting the rhythm or routine of working hours